Die kovariante van opbrengs as teeltkriteria by mielies - Laubscher, F. X.(Franciscus Xavierus),1906-1972 (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (D. Sc. Agric) -- Universiteit van Stellenbosch, 1954.